“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Identification and prediction of standard times in machining for precision steel tubes through the usage of data analytics - Weller, Julian; Roesmann, Daniel; Eggert, Sönke; von Enzberg, Sebastian; Gräßler, Iris; Dumitrescu, Roman (Procedia CIRP)

An Integrative View of the Transformations towards Sustainability and Digitalization: The Case for a Dual Transformation - Kürpick, Christian; Rasor, Anja; Scholtysik, Michel; Kühn, Arno; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Identification and prediction of standard times in machining for precision steel tubes through the usage of data analytics - Weller, Julian; Roesmann, Daniel; Eggert, Sönke; von Enzberg, Sebastian; Gräßler, Iris; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Design of individual simulation games in manufacturing companies for game-based learning - Machon, Fabian; Gabriel, Stefan; Latos, Benedikt; Holtkötter, Christoph; Lütkehoff, Ben; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Process Mining Data Canvas: A method to identify data and process knowledge for data collection and preparation in process mining projects - Brock, Jonathan; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Targeted-oriented selection of engineering methods - Wilke, Daria; Schierbaum, Anja; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Stakeholder-oriented Elaboration of Artificial Intelligence use cases using the example of Special-Purpose engineering - Humpert, Lynn; Wäschle, Moritz; Horstmeyer, Sarah; Anacker, Harald; Dumitrescu, Roman; Albers, Albert (Procedia CIRP)
Keywords: General Medicine

A systematic literature review on the Digital Twin of the factory in the context of the product and factory lifecycle - Cieply, Jonas; Disselkamp, Jan-Philipp; Dyck, Florian; Alturk, Waddah; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Development of a modular architecture for complex mechatronic systems - Seidenberg, Tobias; Disselkamp, Jan-Philipp; Jürgenhake, Christoph; Grobbel, Daniel; Dumitrescu, Roman; Papanikolaou, Apostolos (Procedia CIRP)
Keywords: General Medicine

Integrated product and production development - a systematic literature review - Disselkamp, Jan-Philipp; Cieply, Jonas; Dyck, Florian; Grothe, Robin; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Systematics for an Integrative Modelling of Product and Production System - Schäfer, Louis; Günther, Matthias; Martin, Alex; Lüpfert, Mariella; Mandel, Constantin; Rapp, Simon; Lanza, Gisela; Anacker, Harald; Albers, Albert; Köchling, Daniel (Procedia CIRP)
Keywords: General Medicine

Virtual Assembly for Engineering – A Systematic Literature Review - Dyck, Florian; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Integrative conceptualization of products and business models for the circular economy: A systematic literature review - Scholtysik, Michel; Koldewey, Christian; Rohde, Malte; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

Identification and prediction of standard times in machining for precision steel tubes through the usage of data analytics - Weller, Julian; Roesmann, Daniel; Eggert, Sönke; von Enzberg, Sebastian; Gräßler, Iris; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Scenario-based Foresight in the Age of Digitalization and Artificial Intelligence – Identification and Analysis of Existing Use Cases - Ködding, Patrick; Ellermann, Kai; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

17 Use Cases for Analyzing Use Phase Data in Product Planning of Manufacturing Companies - Meyer, Maurice; Panzner, Melina; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Why make it hard? - Usage of aggregated statistical data for risk assessment of damage scenarios in the context of ISO/SAE 21434 - Japs, Sergej; Kargl, Frank; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Requirements analysis for an intelligent workforce planning system: a socio-technical approach to design AI-based systems - Gabriel, Stefan; Bentler, Dominik; Grote, Eva-Maria; Junker, Caroline; Wendischhoff, David Meyer zu; Bansmann, Michael; Latos, Benedikt; Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Cross-industry methods for strategic planning of the digital transformation of small and medium sized enterprises - Förster, Magdalena; Kürpick, Christian; Hobscheidt, Daniela; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Security- and Safety-Driven Functional Architecture Development Exemplified by Automotive Systems Engineering - Kharatyan, Aschot; Günther, Matthias; Anacker, Harald; Japs, Sergej; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Method for direct end customer integration into the agile product development - Humpert, Lynn; Röhm, Benjamin; Anacker, Harald; Dumitrescu, Roman; Anderl, Reiner (Procedia CIRP)
Keywords: General Medicine

Collaborative Modeling of Interoperable Digital Twins in a SoS Context - Göllner, Denis; Rasor, Rik; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Business-to-Analytics Canvas - Translation of Product Planning-Related Business Use Cases into Concrete Data Analytics Tasks - Panzner, Melina; Meyer, Maurice; Enzberg, Sebastian von; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Value Creation Framework and Roles for Smart Services - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Information Model for Hybrid Prototyping in Design Reviews of Assembly Stations - Gräßler, Iris; Roesmann, Daniel; Hillebrand, Stefan; Pottebaum, Jens (Procedia CIRP ICME)
Keywords: General Medicine

Influence of the incident angle on the OCT measurement during remote laser beam welding - Werner, Matthias; Wagner, Jonas; Ribbeck, Florian; Hensel, Simon; Goth, Klaus; Graf, Thomas; Meschut, Gerson (Procedia CIRP)
Keywords: General Medicine

Microstructure and corrosion properties of PBF-LB produced carbide nanoparticles additivated AlSi10Mg parts - Kusoglu, Ihsan Murat; Vieth, Pascal; Heiland, Steffen; Huber, Florian; Lüddecke, Arne; Ziefuss, Anna Rosa; Kwade, Arno; Schmidt, Michael; Schaper, Mirko; Barcikowski, Stephan; Grundmeier, Guido (Procedia CIRP)
Keywords: General Medicine

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Skill-based worker assignment in a manual assembly line - Gräßler, Iris; Roesmann, Daniel; Cappello, Chiara; Steffen, Eckhard (Procedia CIRP Design)

Maturity-based Development of Strategic Thrusts for Socio-technical Risks - Menzefricke, Joern Steffen; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Maturity-based Development of Strategic Thrusts for Socio-technical Risks - Menzefricke, Jörn Steffen; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Festigkeitssteigerung von Aluminiumblechformteilen der 5000-Serie durch Erweiterung der Formgebungsgrenzen stark kaltverfestigter Ausgangswerkstoffe - Camberg, Alan Adam
Leichtmetalle mit einem breiten Eigenschaftsspektrum gewährleisten die Realisierung ressourcenschonender Produkte und ermöglichen die Intensivierung sortenreiner Kreislaufwirtschaften. Die vorliegende Arbeit untersucht einen wärmeunterstützten Ansatz zur Erhöhung der Formgebungsgrenzen stark kaltverfestigter AlMg4,5 Blechwerkstoffe bei gleichzeitiger Beschränkung des Festigkeitsverlustes durch Erholungseffekte. Experimentelle Untersuchungen stellen eine wissenschaftlich fundierte Erkenntnisbasis über die werkstofftechnischen Wirkzusammenhänge des untersuchten Prozesses dar. Gepaart mit an realen Bauteilgeometrien validierten numerischen Simulationsmodellen legt diese Arbeit einen methodischen Grundstein für die industrielle Umsetzung des hier untersuchten Blechumformprozesses. Die erzielte mittlere Dehngrenze des exemplarisch untersuchten Bauteils übersteigt die Dehngrenze eines konventionellen AlMg4,5 Werkstoffes um 190 %. Mit 320 MPa entspricht sie dem Festigkeitsniveau des walzharten Blechhalbzeuges im Lieferzustand, ein Wert, der nach dem aktuellen Stand der Technik auf Bauteilebene ausschließlich mit aushärtbaren AlMgSi Legierungen darstellbar ist.
Keywords: Aluminium; Blechumformung; AlMg; Materialmodellierung; Duktiles Versagen; Halbwarmumformung; Automobil; Leichtbau; Uni-Alloy; 5000-Serie; 5182; GISSMO

V-model based development of cyber-physical systems and cyber-physical production systems - Gräßler, Iris; Wiechel, Dominik; Roesmann, Daniel; Thiele, Henrik (Procedia CIRP)
Challenges of the development of mechatronic systems and corresponding production systems have increased steadily. Changes are primarily due to increased product complexity and the connection to the internet of things and services, enabling Cyber-Physical Systems (CPS) and Cyber-Physical Production Systems (CPPS). Major innovations of the revised VDI guideline 2206 for developing mechatronic systems are systems thinking as a core element and six checkpoints for structuring deliverables along the V-Model. These checkpoints serve for orientation in result progress and thus enable a structured and complete development process. However, tasks and checkpoints of the new guideline focus on the product development itself without integrating the development of related CPPS, enabling optimization simultaneously to system development. Implications are derived by a three-step analysis. The paper at hand contributes fundamental extensions of the checkpoint questions regarding integrated CPPS development. These questions provide methodical support for system developers of CPPS for CPS by enabling the project manager to check the status, schedule further development steps and evaluate the maturity of the whole, integrated development.
Keywords: Cyber-Physical Production System (CPPS); V-Model; Product System Development; Integrated Development; VDI 2206

Integrating human factors in the model based development of cyber-physical production systems - Gräßler, Iris; Wiechel, Dominik; Roesmann, Daniel (Procedia CIRP)
In order to optimize production processes and to avoid errors, it is not only necessary to automate processes, but also to integrate workers with their individual personality and skill profiles. For this purpose, human factors should be considered in the entire design process. The integrated view of mental human models, the cognitive demand of the working environment and the automation design is essential. Human-System Integration (HSI) constitutes a promising approach. Current model-based approaches offer possibilities to analyze and optimize tasks within an overall system, but they still lack integration. This leads to the research question: How can human factors be integrated into a system model of a socio-technical, Cyber-Physical Production System? The paper at hand contributes an approach of human factor integration into the procedure of Model-Based Systems Engineering for Cyber-Physical Production Systems (CPPS). The approach combines a system model of a CPPS with HSI concepts. In accordance to the benefits of MBSE, SysML is selected to integrate human factors in the development process of a CPPS. The approach is divided into five steps, which includes the extension of the SysML meta model. This allows the optimization of skill-based human-machine interaction. Defined HSI-Profiles enable system developers to integrate employee requirements at early stages within the development process. The approach is demonstrated by the maintenance of a 3D-Printer as a case example. This research enables system developers to depict individual workers with the help of the developed concepts and systematically integrate them into the development process of a CPPS.

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Framework and Functionality Patterns for Smart Service Innovation - Koldewey, Christian; Meyer, Maurice; Stockbrügger, Patrick; Dumitrescu, Roman; Gausemeier, Jürgen (Procedia CIRP)

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

The impact of the 4th industrial revolution on the design fields of innovation management - Niewöhner, Nadine; Asmar, Laban; Röltgen, Daniel; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Significance and Challenges of Data-driven Product Generation and Retrofit Planning - Massmann, Melina; Meyer, Maurice; Dumitrescu, Roman; Enzberg, Sebastian von; Frank, Maximilian; Koldewey, Christian; Kühn, Arno; Reinhold, Jannik (Procedia CIRP)

Product life cycle cost approach for modular lightweight design - Gräßler, Iris; Yang, Xiaojun (Procedia CIRP - Proceedings of the 29th CIRP Design Conference, Band 84)
Today, many companies are facing a continually growing global competition, increasing individual requirements and a demand for shorter development times. In order to deal with these challenges, they respond with an increasing number of product variants, which are managed through variants management methods like modularization. Manufacturers of mobility solutions are also facing higher demands regarding environmental protection and sustainability. Therefore, energy consumption plays a key role in current considerations of mobility solutions and the whole life cycle of a product is considered for controlling and cost calculation. Lightweight design plays a major role for achieving objectives regarding a reduced energy consumption and fulfilling a high functionality of mobility solutions. Modular lightweight design combines the advantages of modularization and lightweight design to enable a modular product with the lowest possible weight. The combination of both methods enables the usage of a cost-efficient lightweight design approach. The presented work will give an overview over the economic aspects and discusses how to utilize the combination of both aspects in a profitable way. The emphasis lies on enabling a cost-efficient design to exploit the potentials of modular lightweight design. The estimation of the profitability is especially important for development decisions in an early phase of product development. It also serves to justify the implementation efforts of an elaborate modular lightweight design approach. Subject of this paper is the development of a model in order to estimate the life cycle costs of modular lightweight products in an early product development stage.

Transformations in product development to enable globally distributed self-organizing production systems - Gräßler, Iris; Hentze, Julian (Procedia CIRP - Proceedings of the 29th CIRP Design Conference, Band 84)
Globally distributed production of products, systems or elements influence both the system architecture and the development process. Influences from logistics, different manufacturing technologies, self-organizing production organization and the efficient use of globally distributed production capacities imply the need to change the design of the system and its development process. Different production sites, for example, require distinctly specified or standardized descriptions of subsystems or elements to be produced. The effort for coordination and formation of interfaces increases, if this fact was not sufficiently taken into account in the design of the subsystem or element. Proximity to the customer implies an important factor for individualized products due to the business model of mass customization. The paper provides overviews of a) transformations in the development process and b) possible solutions for the effective usage of distributed self-organizing production systems. Resulting risks and opportunities from the viewpoint of product engineering are analyzed. Implications for the application of the interdisciplinary development method of the V-model from VDI 2206 guideline are discussed. The structured and established form of the guideline helps to point out which development steps are influenced by globally distributed self-organizing production systems.